Analysis of Students' Mathematical Creative Thinking Ability in Solving Open-Ended Questions Based on Their Self-Concept - Palwa, Nopita; Inayah, Sarah; Septian, Ari; Larsari, Vahid Norouzi (EDUPEDIA Publisher, 2024)
To find out students' mathematical creative thinking abilities, this can be done by giving students open-ended problems. The aim of this research is to describe students' mathematical creative thinking abilities in solving open-ended problems when viewed from their self-concept. This type of research is qualitative descriptive research. The subject selection technique used in this research was purposive sampling. The subjects of this research consisted of one student with a high self-concept category, one student with a medium self-concept category, and one student with a low self-concept. Data collection methods in this research include questionnaire methods and tests. And the data analysis techniques used include: analysis of mathematical self-concept questionnaires, analysis of open-ended mathematics questions. The research results show that students with a high self-concept category can fulfill all aspects of creative thinking abilities, including fluency, flexibility and originality, so that their mathematical creative thinking abilities are also high. In contrast to students with moderate self-concept, it was found that their creative thinking abilities were low and students with low self-concept actually had moderate mathematical creative thinking abilities. So it can be concluded that based on this research, it shows that students' self-concept does not always describe students' mathematical creative thinking abilities in solving open-ended problems.